Liquidity in the German stock market - Thomas Johann; Stefan Scharnowski; Erik Theissen; Christian Westheide; Lukas Zimmermann (University of Cologne, Centre for Financial Research (CFR), 2019)
This paper presents the most extensive analysis of liquidity in the German equity market so far. We examine the evolution of liquidity over time, the determinants of liquidity, and commonality across liquidity measures and countries. We make use of a new publicly available dataset, the Market Microstructure Database Xetra (MMDB-Xetra). We find that liquidity has generally increased over time, and that in times of crisis liquidity is lower and the volatility of liquidity is significantly higher. Commonality in liquidity is highest during the financial crisis. We also find significant commonality between liquidity in the US and the German equity markets.
Keywords: G10; G14; G15; 330; Market Microstructure; Liquidity; Volatility; Germany; Xetra